2004
DOI: 10.1038/nmat1263
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic lattice distortions in biogenic aragonite

Abstract: Composite biogenic materials produced by organisms have a complicated design on a nanometre scale. An outstanding example of organic-inorganic composites is provided by mollusc seashells, whose superior mechanical properties are due to their multi-level crystalline hierarchy and the presence of a small amount (0.1-5 wt%) of organic molecules. The presence of organic molecules, among other characteristics, can influence the coherence length for X-ray scattering in biogenic crystals. Here we show the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
177
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(210 citation statements)
references
References 17 publications
21
177
2
2
Order By: Relevance
“…While Raman spectroscopy cannot be used to quantify the unit cell parameters with the precision of XRD, we expect the unit cell changes to manifest in the Raman ν 1 peak as (1) a decrease in FWHM due to decreased disorder, and (2) an increase in wavenumber due to the shorter bond lengths, and thus higher frequency vibrations, in the contracted unit cell. Indeed, this is exactly what we observed after annealing JCp-1, entirely consistent with the results of Pokroy et al (2004) and subsequent studies (reviewed in Zolotoyabko, 2017).…”
Section: Insights From Annealing Experimentssupporting
confidence: 93%
See 2 more Smart Citations
“…While Raman spectroscopy cannot be used to quantify the unit cell parameters with the precision of XRD, we expect the unit cell changes to manifest in the Raman ν 1 peak as (1) a decrease in FWHM due to decreased disorder, and (2) an increase in wavenumber due to the shorter bond lengths, and thus higher frequency vibrations, in the contracted unit cell. Indeed, this is exactly what we observed after annealing JCp-1, entirely consistent with the results of Pokroy et al (2004) and subsequent studies (reviewed in Zolotoyabko, 2017).…”
Section: Insights From Annealing Experimentssupporting
confidence: 93%
“…We then annealed a subset of JCp-1 and the abiogenic samples f03 and f06 following the procedure of Pokroy et al (2004). The samples were heated in an oven at 140 • C for 16 h and then allowed to cool to room temperature before Raman analyses.…”
Section: Annealing Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, based on the facts that the organic matters extracted from the nacres could effectively induce the nucleation and grow-up of the calcium carbonate and the types and contents of organic matters decided the degree of order of inorganic crystals [19][20][21][22][23], previous research results [24][25][26] concluded that the organic matters could induced lattice distortion of aragonite and lowered its degree of order and nanometer size effects of aragonite could lowered its degree of order also. In this scenario, comparing the 862 cm −1 IR peak related to aragonite of the samples with the peak of standard inorganic origin aragonite, the obvious blue shift (7.5 cm −1 ) indicated that there existed complex coordination effects between the organic and inorganic matters.…”
Section: Discussionmentioning
confidence: 99%
“…Many hard biological materials such as shells and bivalves contain a mineral phase. A new direction consists of starting at the atomic / molecular level through self-assembly and proceeds up in the dimensional scale, incorporating the hierarchical complexity of biological materials (Pokroy et al, 2004(Pokroy et al, , 2006a(Pokroy et al, , 2006b). These new structures that have potential applications in a number of areas, including quantum dots, photonic materials, drug delivery, tissue engineering, and genetically engineered biomaterials.…”
mentioning
confidence: 99%